Language of Transducer Manipulation: Codifying Terms for Effective Teaching. (1st January 2016) - Bahner, David P.; Blickendorf, J. Matthew; Bockbrader, Marcia; Adkins, Eric; Vira, Amar; Boulger, Creagh; Panchal, Ashish R.
Abstract : There is a need for consistent, repetitive, and reliable terminology to describe the basic manipulations of the ultrasound transducer. Previously, 5 basic transducer motions have been defined and used in education. However, even with this effort, there is still a lack of consistency and clarity in describing transducer manipulation and motion. In this technical innovation, we describe an expanded definition of transducer motions, which include movements to change the transducer's angle of insonation to the target as well as the location on the body to optimize the ultrasound image. This new terminology may allow for consistent teaching and improved communication in the process of image acquisition.